UVB-Induced necroptosis of the skin cells via RIPK3-MLKL activation independent of RIPK1 kinase activity - Tairan Hu; Xiaodong Lai; Li Li; Yi Li; Meng Wang; Haini Zhang; Yan Yang; Chong Zhang; Yan Yan; Baoxi Wang (Cell Death Discovery)
Abstract Ultraviolet B (UVB) is recognized for inducing inflammation and death of keratinocytes through the activation of death receptors and pattern recognition receptors (PRRs). Receptor-interacting protein kinase 1 (RIPK1) and RIPK3 play pivotal roles in mediating necroptosis, which can be triggered by the activation of specific death receptors and PRRs. In this study, we observed a reduction of RIPK1 protein after UVB exposure which led to activation of Nuclear factor-kappa B (NF-κB) in HaCaT cells. This activation, in turn, promoted the production of IL-1β and TNF-α. However, RIPK1 kinase remained inactive and did not participate in cell death. Interestingly, UVB radiation triggered the activation of RIPK3 independently of RIPK1 kinase activity and subsequently induced phosphorylation of mixed-lineage kinase domain-like protein (MLKL), culminating in necroptosis and inflammation of the skin. At the same time, UVB-induced activation of RIPK3 also played a role in promoting the mitochondrial apoptotic pathway of Keratinocytes. In conclusion, UVB irradiation initiates an inflammatory response via RIPK1 pathway without necessitating its enzymatic activity. Simultaneously, RIPK3 can be activated by UVB exposure independently of RIPK1’s activity, resulting in necroptosis and inflammation of the skin.